The concept of the authority at Turks - Mohammed Abdulabbas Naji, Abbas khamies Abood El-zubydi, (Opción, 2019)
The study aims at focusing the light on the political system of tribes and clarifying the authority of the Supreme Khan via comparative qualitative research methods. As a result, the supreme ruler of the tribe was called (Khan) and was receiving ambassadors and holds treaties with neighbouring forces such as China and the Sassanid state and the Arab Islamic state later. In conclusion, the nature of the military conflicts that sometimes took place between the Turkish tribes or some of the Khans to take power by force led to the dispersal and rupture of the Turkish nation.